Criminal law - Roach, Kent (Essentials of Canadian law, 2022)
"The eighth edition of Criminal Law has been thoroughly updated to include new developments. It includes a detailed discussion of R v Brown striking down restrictions on the extreme intoxication defence and the likely parliamentary reply, and Parliament’s reply in Bill C-28. It also examines changes in jury selection upheld in R v Chouhan; important decisions on fault, such as R v Zora, R v Javanmardi, R v Chung, and R v Goforth; and assesses R v Cowan on parties. The discussion of sexual assault has been updated to take into account R v Barton and the possible implications of R v Morrison. The Supreme Court’s first decision under the amended self-defence provisions in R v Khill is reviewed. This new edition also has been revised to include important decisions from the Ontario and Nova Scotia Courts of Appeal on sentencing Black offenders, as well as the Supreme Court’s striking down of mandatory minimum fine surcharges and stacking of twenty-five-year periods of parole ineligibility."-- Provided by publisher.